Hodnocení výsledků jodové profylaxe v ceské republice - Zamrazil, V; Cerovská, J; Bílek, R; Dvoráková, M; Nemecek, J; Vavrejnová, V; Zamrazilová, H (Casopis lekaru ceskych, 2007)
BACKGROUND: Improvement of system of iodine prophylaxis in Czech Republic resulted in compensation of iodine deficiency. Effects of increased iodine intake on the status of thyroid gland (volume, function, autoimmune disorders) should be determined. The aim of the study was to evaluate those effects in an epidemiological survey. METHODS AND RESULTS: A randomly selected sample of adult population (18-65 years old) from 3 regions was investigated using the same methods at the interval of 5 years. A significant increase of ioduria was proved with the marked increase of prevalence of high category (over 300 ug of I per 100 mL of urine). Volume of the thyroid gland decreased significantly in women, not in men. No significant changes of TSH were observed, however FT4 level slightly, but significantly increased. CONCLUSIONS: Repeated epidemiological survey of the randomly selected sample of adult population in 3 regions verified the effectiveness of improved iodine prophylaxis with not unequivocally positive increase of high (supraphysiological) category of ioduria. Decrease of thyroid volume was proved in women only, a tendency of mild (clinically not important) increase of thyroid function was also observed.
Keywords: senioři; thyroxin; mladiství; Česká republika; potravní doplňky; Middle Aged; jod; mužské pohlaví; Thyroid Gland; Adult; Czech Republic; Thyrotropin; thyreotropin; Organ Size; velikost orgánu; zdravotní výchova; ženské pohlaví; Humans; štítná žláza; Health Education; Dietary Supplements; lidé středního věku; Iodine; Thyroxine; dospělí; Female; Aged; Adolescent; lidé; Male